The Relationship Between Reading Self-Efficacy and Perceived Use of Reading Strategies Among Saudi EFL Students - Altumigah, Effat S.; Alkhaleefah, Tarek A. (International Journal of Linguistics, 2022)
This study aimed to explore the relationship between reading self-efficacy and perceived use of reading strategies among Saudi EFL senior high school female students. With a correlational research design, the study data were collected by administrating two questionnaires: The Reader Self-Perception Scale (RSPS) questionnaire adapted from Henk & Melnick (1995), and the Survey of Reading Strategies (SORS) adapted from Li & Wang (2010). The two instruments were administrated to 90 Saudi senior high school female students randomly selected from three different public schools in Riyadh, Saudi Arabia. The data were analyzed using Pearson correlation coefficient and regression analysis to determine the relationship between self-efficacy and EFL learners’ perceived use of reading strategies. The study findings revealed how Saudi senior high school students possessed more low and moderate levels than high levels of reading self-efficacy, and that metacognitive processes were the most frequently used strategies among cognitive and compensation strategies. In addition, a positive relationship between students’ reading self-efficacy and perceived use of reading strategies was detected. Pedagogical implications of the study findings and its recommendations were presented and discussed.